PENGEMBANGAN MANEJEMEN KURIKULUM PONDOK PESANTREN MODERN ADH-DHUHAA BERBASIS YATIM & DU'AFA - naryo Sunaryo Putro (Tarbawi : Jurnal Pendidikan Islam, 2020)
This study aims to describe the implementation of curriculum management development Adh-Dhuhaa Sukoharjo Islamic Boarding School. This study uses qualitative methods with interactive data analysis techniques with data reduction, data presentation, and drawing conclusions or verification. Research informants are boarding school caregivers, principals, teachers, guardians of students. The results of the study revealed that the development of Adh-Dhuhaa boarding school curriculum management began with a plan that involved all elements of the pesantren and schools; in the curriculum planning stage all the interests of santri education and its potential were included in the planning. The implementation of curriculum management development went well, although there was an unwritten curriculum that could run because of assistance from the santri organization (OSPA) and the evaluation of curriculum management development followed the official program, the Ministry of Religion and the local curriculum. Keywords: development, curriculum, Islamic boarding school  Abstrak Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan pengembangan manajemen kurikulum Pondok Pesantren Adh-Dhuhaa Sukoharjo. Penelitian ini menggunakan metode kualitatif dengan teknik analisis data interaktif dengan reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Informan penelitian adalah pengasuh pesantren, kepala sekolah, guru, wali santri. Hasil penelitian diketahui bahwa pengembangan manajemen kurikulum pondok pesantren Adh-Dhuhaa diawali dengan perencanaan yang melibatkan semua unsur pesantren dan sekolah, dalam tahapan perencanaan kurikulum semua kepentingan pendidikan santri dan potensinya di masukkan ke dalam perencanaan. Pelaksanaan pengembangan manajemen kurikulum ini berjalan dengan baik, meskipun ada kurikulum yang tak tertulis bisa berjalan karena bantuan dari organisasi santri (OSPA) dan evaluasi pengembangan manajemen kurikulum ini mengikuti program dinas, kemenag dan kurikulum lokal. Kata Kunci: pengembangan, kurikulum, pondok pesantren